Shifting notions of funerals among Africans: a case of the Shona of Zimbabwe - Sipeyiye, Macloud (Africa Institute for Culture, Peace, Dialogue and Tolerance Studies, 2019)
Death among African cultures is a sacred phenomenon. It is so held because death is believed to proffer the inevitable transformation of the physical existence into spiritual realm loaded with meaning that often goes beyond human comprehension. The metaphysical connections make it one of the most enigmatic experiences warranting some burdensome traditional rites, strictly laid down burial procedures and a grief-laden atmosphere throughout the funeral proceedings. The metaphysical dimension of death is the basis of religious conceptions, beliefs and practices in African Traditional Religions (ATRs). However, there have been strange things that occur at funerals that are not in tune with what is expected of a funeral in the eyes of the traditional Africans. Mourners come in the mood of competition for social recognition punctuated by their great taste of fashion and the bereaved families compete to find the best caterers available. Those with anti-social economic engagements such as armed robbers appropriate funerals appropriate funeral platforms to endorse their status. They are also undeterred by their ‘trades’ as they always want to make funerals of their deceased colleagues grandiose “send offs”. As a result, the sacredness of death is gradually, but surely diminishing. Using the case of the Shona of Zimbabwe, this Chapter argues that funerals among Africans have taken a new twist in recent times becoming contested spaces for the crafting of new socio-economic identities in the fast transforming societies of Africa. In the process, funerals are losing their cultural and religious significance. Using a socio-historical analysis the paper examines the changing perceptions on funerals in different social and historical contexts. The paper looks at the traditional Shona’s view of death and the dead, conduct of funerals and finally discusses the emerging trends on funerals making reference to other societies of Africa.